PENGEMBANGAN MEDIA INTERAKTIF EDUCAPLAY UNTUK MENINGKATKAN PEMAHAMAN PERSAMAAN DAN LAWAN KATA KELAS V SEKOLAH DASAR - Siti Amla Zuchrifa Aisyah; Arita Marini; Gusti Yarmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an interactive learning media based on Educaplay for teaching synonyms and antonyms to fifth-grade elementary school students. The research was motivated by the need to create a high-quality learning media that can improve students' understanding of the material, which remains low due to conventional teaching methods. This study employed the ADDIE development model, focusing on the first three stages: analysis, design, and development. Data were collected through observation, interviews, and document analysis. The media was designed as a series of interactive activities, such as quizzes and word-matching tasks with audio features, to enhance engagement and comprehension. The validation process involved a subject matter expert and a media expert. The results showed that the media received a validity score of 88% from both validators, placing it in the “Very Valid” category. Therefore, the Educaplay-based media is considered suitable as an engaging and interactive alternative for teaching Indonesian, especially in vocabulary topics such as synonyms and antonyms.